TELAAH SINERGITAS FUNGSI SOSIAL BAITUL MAAL DAN FUNGSI BISNIS BAITUL TAMWIL PADA KANINDO SYARIAH - RIJALLUDIN, MUHAMMAD (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Baitul maal wa Tamwil is a financial institution with the concept of shariawhich is born as an option that combines the concept of maal and tamwil in one institution activity. Kanindo is one of the simplest models of sharia financial institutions that currently appear and drown in Indonesia. The existence of several LKS with significant amount in some regions in Indonesia is not supported by supporting factors that allow to keep developing and running well. The researcher aims to explore how far Kanindo sharia in carrying out the functions that exist in Baitu Mal and Baitul tamwil, and the synergy between them. This research usesqualitative research approach and sourced from primary data. Determination of informants using nonprobability sampling with purposive sampling method. The result of this research is in fact in BMT Kanindo Syariah not running synergy. The more dominant function used is the business function. There are several factors that must be considered is by preparing the supporting infrastructure in order to improve management. It is necessary to improve both the personal management, staff, and employees in order to increase the capacity of personnel to understandand implement the functions that exist within the sharia financial institution.Keywords: PT Kanindo Syariah Dau, synergy, social function, business function